Gender and solid waste management in the informal sector of Bulawayo, Zimbabwe - Jerie, Steven (Midlands State University, 2014)
This paper aims at assessing the role of gender in solid waste management in the informal sector in the high density suburbs of Bulawayo, the second largest city in Zimbabwe. The quantitative approach used in data collection involved physical characterisation of waste for composition analysis and the measurement of amounts of waste generated in the informal sector. Questionnaire surveys were also used to gather data on waste management practices by gender. Interviews, focus group discussions and participant observations were employed for the collection of qualitative data. Results showed the dominance of women in trades such as food catering and vending, clothes retailing, basket making and textiles while men dominated in motor mechanics, carpentry, welding, tinsmith, spare parts and door and window frame making. Generally, more solid waste is generated in enterprises operated by men than those operated by women. There is generally poor management of waste in the home industries, however, there is a greater level of cleanliness in the enterprises run by women who engage in waste reduction practices such as waste picking and recycling. It is thus necessary to incorporate gender perspectives in all developmental efforts including solid waste management in the informal sector.